Macro-infaunal community structure on the Chatham Rise, Southwest Pacific - Rachel Hale (PANGAEA, 2025)
We examined changes in environmental parameters following an experimental benthic disturbance using a modified plough (estimated 15 cm penetration) on the Chatham Rise (~450 m depth), Aotearoa/New Zealand. Sediment core retrievals were undertaken using an Oceans Instruments MC-800 multicorer fitted with six 70 cm long polycarbonate core tubes with 9.52 cm internal diameter that took place pre-disturbance on 16-17 June 2019 (voyage TAN1903), post-disturbance on 24-25 June 2019 (TAN1903) and one-year post-disturbance on 14-19 June 2020 (TAN2005). In order to determine any background changes in the larger surrounding area between years (2019, 2020), an additional reference site with similar hydrographic and sediment attributes (REF, depth = 455 m), located approximately 15 km to the north-west of the Butterknife (Figure 1B), was also sampled in the pre-disturbance period (n = 2, TAN1903) and one-year post-disturbance (n = 3, TAN2005). Sediment flux measurements were taken from subsampled multicores (0-10 cm layer) using sealed stirred aquaria maintained at bottom water conditions in the controlled temperature laboratory on RV Tangaroa. After the flux incubations were terminated, the macro-infauna community (retained on 300 μm sieve) in each sediment core were fixed in a 10% formalin (4% formaldehyde) solution buffered with seawater. Macro-infaunal individuals were identified to family, or the lowest taxonomic level possible and counted to obtain macro-infauna abundance. For the estimation of biomass (g), fauna were wet weighed (blotted dry on absorbent paper to remove excess liquid). The number of taxa per aquaria (at the lowest identifiable taxonomic level) was counted to obtain a value of taxa richness and Shannon diversity (base e) was calculated.
In: Hale, R (2025): Effects of an experimental in situ seabed disturbance on deep-sea benthic ecosystem function and macro-infaunal community structure on the Chatham Rise, Southwest Pacific [dataset bundled publication]. PANGAEA, https://doi.org/10.1594/PANGAEA.975610